From Antimicrobial to Anticancer Peptides: The Transformation of Peptides - Qin, Yuan; Qin, Zuo D.; Chen, Jing; Cai, Che G.; Li, Ling; Feng, Lu Y.; Wang, Zheng; Duns, Gregory J.; He, Nong Y.; Chen, Zhe S.; Luo, Xiao F. (Recent Patents on Anti-Cancer Drug Discovery, 2019)
Background: Antimicrobial peptides play an important role in the innate immune system. Possessing broad-spectrum antibacterial activity, antimicrobial peptides can quickly treat and kill various targets, including gram-negative bacteria, gram-positive bacteria, fungi, and tumor cells. Objective: An overview of the state of play with regard to the research trend of antimicrobial peptides in recent years and the situation of targeting tumor cells, and to make statistical analysis of the patents related to anticancer peptides published in recent years, is important both from toxicological and medical tumor therapy point of view. Methods: Based on the Science Citation Index Expanded version, the Derwent Innovation Index and Innography as data sources, the relevant literature and patents concerning antimicrobial peptides and anticancer peptides were analyzed through the Thomson Data Analyzer. Results of toxicologic and pharmacologic studies that brought to the development of patents for methods to novel tumor drugs were analyzed and sub-divided according to the specific synthesis of anticancer peptides. Results: The literature and patent search data show that the research and development of global antimicrobial peptides and anticancer peptides has been in an incremental mode. Growing patent evidence indicate that bioinformatics technology is a valuable strategy to modify, synthesize or recombine existing antimicrobial peptides to obtain tumor drugs with high activity, low toxicity and multiple targets. Conclusion: These findings may have important clinical implications for cancer treatment, especially in patients with conditions that are not currently treatable by other drugs, or that are resistant to existing cancer drugs.
Keywords: anti-tumor